My Pencil is my Friend/I Keep Him to the End-- -The First Graderand the Social Narrative of Literacy, Agency and Ageing in Postcolonial Kenya (Global Journal of Human-Social Science, 2017)
Ecological theories of ageing suggest that a unique combination of factors such as personal competence and environmental characteristics influence an older adult s sense of autonomy and optimal level of functioning in society One does not usually factor in possibilities of acquiring literacy as a crucial aspect of the environmental resources necessary for supporting an older adult s aspirations Through a close reading of James Chadwick s film The First Grader 2010 which narrates Kimani Ng ang a Maruge s struggle for acquiring literacy through attending primary school amidst much socio-political resistance I shall be seeking an appropriate heuristic for comprehending an older adult s desire for literacy and the possibilities of an environment reengineered to provide the same by the older adult himself My study shall also endeavour to identify the little narratives Beth Daniells 1999 in the film that critique the grand narrative of literacy promoted by the postcolonial state of Kenya to highlight inherent ageist assumptions that often unthinkingly exclude the aged from state narratives of progress for all
Keywords: ecology; ageing; autonomy; agency; literacy; narrative; environment; postcolonial